Auditoría de Gestión al Gobierno Autónomo Descentralizado Municipal de Chambo, periodo 2021. - Guaraca Morocho, Erika Tatiana (2023)
Management Audit of the Autonomous Decentralized Municipal Government of Chambo, period 2021 The purpose of this performance audit of the Autonomous Decentralized Municipal Government of Chambo, Period 2021, is to measure the efficiency, effectiveness and compliance with the budget that has been executed within the institution, thus helping the public entity to make decisions since it will have a clearer vision of its own budget execution. For the development of the audit, we proceeded to review the state of budget execution at the close of 2021, the statement of results and the annual operating plan for the period 2021, therefore, management indicators were applied that measured, by means of percentages of compliance, efficiency and effectiveness, as well as compliance with the execution of the annual budget. Internal control questionnaires were also used to evaluate the level of risk and trust that exists within the officials of the Autonomous Decentralized Municipal Government of Chambo, which has allowed identifying the following findings: lack of budget execution, there is a training plan, but it is not adequate and, finally, it is found that indicators that measure the management of the GAD are not being developed. It is recommended that the suggestions made in the final report on the communication of results of the performance audit be applied correctly, so that timely and efficient decisions can be made for the correct performance of the institution.